Mechanisms Involved in Extraterritorial Facial Pain following Cervical Spinal Nerve Injury in Rats. Issue 1 (10th February 2011) - Kobayashi, Azusa; Shinoda, Masamichi; Sessle, Barry J; Honda, Kuniya; Imamura, Yoshiki; Hitomi, Suzuro; Tsuboi, Yoshiyuki; Okada-Ogawa, Akiko; Iwata, Koichi
Background: The aim of this study is to clarify the neural mechanisms underlying orofacial pain abnormalities after cervical spinal nerve injury. Nocifensive behavior, phosphorylated extracellular signal-regulated kinase (pERK) expression and astroglial cell activation in the trigeminal spinal subnucleus caudalis (Vc) and upper cervical spinal dorsal horn (C1-C2) neurons were analyzed in rats with upper cervical spinal nerve transection (CNX). Results: The head withdrawal threshold to mechanical stimulation of the lateral facial skin and head withdrawal latency to heating of the lateral facial skin were significantly lower and shorter respectively in CNX rats compared to Sham rats. These nocifensive effects were apparent within 1 day after CNX and lasted for more than 21 days. The numbers of pERK-like immunoreactive (LI) cells in superficial laminae of Vc and C1-C2 were significantly larger in CNX rats compared to Sham rats following noxious and non-noxious mechanical or thermal stimulation of the lateral facial skin at day 7 after CNX. Two peaks of pERK-LI cells were observed in Vc and C1-C2 following mechanical and heat stimulation of the lateral face. The number of pERK-LI cells in C1-C2 was intensity-dependent and increased when the mechanical and heat stimulations of the face were increased. The decrements of head withdrawal latency to heat and head withdrawal threshold to mechanical stimulation were reversed during intrathecal (i.t.) administration of MAPK/ERK kinase 1/2 inhibitor PD98059. The area of activated astroglial cells was significantly higher in CNX rats (at day 7 after CNX). The heat and mechanical nocifensive behaviors were significantly depressed and the number of pERK-LI cells in Vc and C1-C2 following noxious and non-noxious mechanical stimulation of the face was also significantly decreased following i.t. administration of the astroglial inhibitor fluoroacetate. Conclusions: The present findings have demonstrated that mechanical allodynia and thermal hyperalgesia occur in the lateral facial skin after CNX and also suggest that ERK phosphorylation of Vc and C1-C2 neurons and astroglial cell activation are involved in orofacial extraterritorial pain following cervical nerve injury.